The Efficacy of Photodynamic Therapy in the Treatment of Halitosis: A Systematic Review - Muhammad Bintang Raja Faleqy; Ma'rifatu Qolbi; Setiabudi, Maria Felicia Louise; Zahara Meilawaty; Amandia Dewi Permana Shita (International Journal of Medical Science and Clinical Research Studies, 2025)
Introduction: Halitosis is a condition of bad breath that can affect the quality of life of sufferers. The main cause of halitosis is the accumulation of bacteria on the dorsum of the tongue that produce volatile sulfur compounds (VSCs). Conventional methods such as the mouthwash and tongue scraping often do not provide long-lasting results and can trigger bacterial resistance. Objective: This literature review provides information on the efficacy of photodynamic therapy in the treatment of halitosis patients. Methods: A literature search was conducted in PubMed, Scopus, Cochrane and ScienceDirect databases with inclusion criteria according to the PICOS framework in the period 2020-2024. Review: Photodynamic therapy (PDT) is an alternative treatment that uses a combination of photosensitizers and light to produce reactive oxygen species that damage bacterial cell membranes. PDT has been widely used in various medical fields, including in the treatment of cancer, infections, and is now being developed for the treatment of halitosis. Discussion: This study revealed that PDT is able to reduce the concentration of microorganisms that cause halitosis on the dorsum of the tongue significantly compared to conventional methods. However, there are several limitations such as uneven penetration of photosensitizers and the possibility of bacterial recolonization in a short time after therapy. Conclusion: PDT is an effective method to reduce bacteria that cause halitosis with a low risk of microbial resistance. However, limitations related to bacterial penetration and recolonization indicate that this therapy needs to be done repeatedly for more sustainable results.